The Effectiveness of Using Problem-Based Learning (PBL) in Mathematics Problem-Solving Ability for Junior High School Students - Febrinna Marchy; Atma Murni; Kartini kartini; Ilham Muhammad (Department of Mathematics Education, Universitas Muhammadiyah Purwokerto, Indonesia, 2022)
This study aims to determine the effectiveness of the Problem Based Learning model in improving students' problem solving abilities. This is a quasi-experimental study using the Nonequivalent Pretest-Posttest Control Group Design. Students in seventh grade at SMP Negeri 32 Pekanbaru comprised the whole study population. In this research, the sample comprised two classes: VII3 as the experimental class and VII1 as the control class. This study utilizes the beginning mathematical ability test (KAM) and the mathematical problem-solving ability test as its instruments. The class of the sample was determined using the KAM test findings. The data were evaluated using the similarity test of two independent sample t-tests, which was preceded by tests for normality and homogeneity of variance. Students who participated in Problem-Based Learning had greater growth in their ability to solve mathematical problems than students who participated in conventional learning.